Quantification of Adequate Bowel Preparation for Screening or Surveillance Colonoscopy in Men - Clark, Brian T; Protiva, Petr; Nagar, Anil; Imaeda, Avlin; Ciarleglio, Maria M; Deng, Yanhong; Laine, Loren (Gastroenterology (New York, N.Y. 1943), 2016)
Bowel preparation is defined as adequate if it is sufficient for identification of polyps greater than 5 mm. However, adequate preparation has not been quantified. We performed a prospective observational study to provide an objective definition of adequate preparation, based on the Boston Bowel Prep Scale (BBPS, which consists of 0-3 points for each of 3 colon segments). We collected data from 438 men who underwent screening or surveillance colonoscopies and then repeat colonoscopy examinations within 60 days by a different blinded endoscopist (1161 colon segments total) at the West Haven Veterans Affairs Medical Center from January 2014 to February 2015. Missed polyps were defined as those detected on the second examination of patients with the best possible bowel preparation (colon segment BBPS score of 3) on the second examination. The primary outcome was the proportion of colon segments with adenomas larger than 5 mm that were missed in the first examination. We postulated that the miss rate was noninferior for segments with BBPS scores of 2 vs those with BBPS scores of 3 (noninferiority margin, <5%). Our secondary hypotheses were that miss rates were higher in segments with BBPS scores of 1 vs those with scores of 3 or of 2. The adjusted proportion with missed adenomas greater than 5 mm was noninferior for segments with BBPS scores of 2 (5.2%) vs those with BBPS scores of 3 (5.6%) (a difference of -0.4%; 95% confidence interval [CI], -2.9% to 2.2%). Of study subjects, 347 (79.2%) had BBPS scores of 2 or greater in all segments on the initial examination. A higher proportion of segments with BBPS scores of 1 had missed adenomas larger than 5 mm (15.9%) than segments with BBPS scores of 3 (5.6%) (a difference of 10.3%; 95% CI, 2.7%-17.9%) or 2 (5.2%) (a difference of 10.7%; 95% CI, 3.2%-18.1%). Screening and surveillance intervals based solely on the findings at the first examination would have been incorrect for 16.3% of patients with BBPS scores of 3 in all segments, for 15.3% with BBPS scores of 2 or 3 in all segments, and for 43.5% of patients with a BBPS score of 1 in 1 or more segments. Patients with BBPS scores of 2 or 3 for all colon segments have adequate bowel preparation for the detection of adenomas larger than 5 mm and should return for screening or surveillance colonoscopy at standard guideline-recommended intervals. Colon segments with a BBPS score of 1 have a significantly higher rate of missed adenomas larger than 5 mm than segments with scores of 2 or 3. This finding supports a recommendation for early repeat colonoscopic evaluation in patients with a BBPS score of 0 or 1 in any colon segment.